The Fundamentals of Accreditation What Do You Need To Know? (Distributed by ERIC Clearinghouse, 2002)
In a series of questions and answers, the Council for Higher Education Accreditation presents the fundamentals of the accreditation process and describes accrediting organizations. Accreditation is a process of external quality review used by higher education to scrutinize colleges, universities, and educational programs for quality assurance and quality improvement. In the United States, accreditation is carried out by private, nonprofit organizations designed for this purpose. These organizations fall into the categories of regional accrediting organizations (there are six), national accreditation organizations that usually review entire institutions, and specialized accrediting organizations that review programs and some single-purpose institutions. The questions and answers describe the accreditation process, the "accrediting" of accrediting organizations themselves, the role of accreditation in distance education, and some aspects of accreditation that have important implications for the future. (SLD)